A Randomized Controlled Trial of Intravenous N-Acetylcysteine in the Management of Anti-tuberculosis Drug–Induced Liver Injury. (26th August 2020) - Moosa, Muhammed Shiraz; Maartens, Gary; Gunter, Hannah; Allie, Shaazia; Chughlay, Mohamed F; Setshedi, Mashiko; Wasserman, Sean; Stead, David F; Hickman, Nicole; Stewart, Annemie; Sonderup, Mark; Spearman, Catherine Wendy; et al.
Abstract: Background: Liver injury is a common complication of anti-tuberculosis therapy. N-acetylcysteine (NAC) used in patients with paracetamol toxicity with limited evidence of benefit in liver injury due to other causes. Methods: We conducted a randomized, double-blind, placebo-controlled trial to assess the efficacy of intravenous NAC in hospitalized adult patients with anti-tuberculosis drug–induced liver injury (AT-DILI). The primary endpoint was time for serum alanine aminotransferase (ALT) to fall below 100 U/L. Secondary endpoints included length of hospital stay, in-hospital mortality, and adverse events. Results: Fifty-three participants were randomized to NAC and 49 to placebo. Mean age was 38 (SD±10) years, 58 (57%) were female, 89 (87%) were HIV positive. Median (IQR) serum ALT and bilirubin at presentation were 462 (266–790) U/L and 56 (25–100) μmol/L, respectively. Median time to ALT <100 U/L was 7.5 (6–11) days in the NAC arm and 8 (5–13) days in the placebo arm. Median time to hospital discharge was shorter in the NAC arm (9 [6–15] days) than in the placebo arm (18 [10–25] days) (HR, 1.73; 95% CI, 1.13–2.65). Mortality was 14% overall and did not differ by study arm. The study infusion was stopped early due to an adverse reaction in 5 participants receiving NAC (nausea and vomiting [3], anaphylaxis [1], pain at drip site [1]). Conclusions: NAC did not shorten time to ALT <100 U/L in participants with AT-DILI, but significantly reduced length of hospital stay. NAC should be considered in management of AT-DILI. Clinical Trials Registration: South African National Clinical Trials Registry (SANCTR: DOH-27-0414-4719). Abstract : N-acetylcysteine did not shorten time to alanine transaminase <100 U/L in a randomized placebo-controlled trial of hospitalized adults with anti-tuberculosis drug–induced liver injury. However, participants who received N-acetylcysteine had shorter hospital stays. Mortality did not differ by study arm.